Liver cirrhosis as a result of chronic hepatitis C - A. A. Sukhoruk; O. A. Gerasimova; E. V. Esaulenko (Журнал инфектологии)
The incidence of chronic hepatitis C in St. Petersburg is 124.4 per 100 000 population. The number of patients with liver cirrhosis is significant.Aim of this study: to examine the demographic, clinical and epidemiological characteristics of patients with cirrhosis in the results of chronic hepatitis C.Materials and methods: 100 patients with cirrhosis due to chronic hepatitis C in age 31–70 years were included. Patients with infection hepatitis viruses A and B, HIV, alcohol abuse, drug addicts, previously received antiviral therapy were excluded. Liver cirrhosis was diagnosed on the basis clinical, laboratory and instrumental investigations.Results: most patients (86,2% male and 81,7% female) are socially adapted. In 23,2% of patients antibodies to hepatitis C virus were first detected simultaneously with the diagnosis of cirrhosis. Medical procedures were the most common route of infection (25,6% male and 57,1% female). Genotype 1 was dominant (65.7%). Viral load over 800 000 IU/ml was detected in 36,7% of patients. ALT activity was normal or not more than 2 upper limit of normal in 59% of patients, AST – 47%. Normal levels of total bilirubin were recorded in 37% of cases.Conclusions: the first detection of antibodies to hepatitis C virus at the stage of cirrhosis, absence of jaundice, normal or low cytolytic activity once again confirms the need for screening for markers of hepatitis C virus. Dominance of genotype 1 is probably due on the one hand with features routes of transmission, and the other – with the speed of transformation chronic hepatitis to cirrhosis.